2018
DOI: 10.5808/gi.2018.16.2.36
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LEF1 as a Susceptibility Locus for Kawasaki Disease in Patients Younger than 6 Months of Age

Abstract: Kawasaki disease (KD) is an acute febrile vasculitis predominately affecting infants and children. The dominant incidence age of KD is from 6 months to 5 years of age, and the incidence is unusual in those younger than 6 months and older than 5 years of age. We tried to identify genetic variants specifically associated with KD in patients younger than 6 months or older than 5 years of age. We performed an age-stratified genome-wide association study using the Illumina HumanOmni1-Quad BeadChip data (296 cases v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 37 More recently, an age-stratified genome-wide association study targeting both Korean and Japanese populations suspected a rare non-synonymous SNP (rs4365796) in the lymphoid enhancer binding factor 1 gene to be a susceptibility gene to specifically affect KD patients younger than 6 months of age. 38 Interestingly, Biezeveld et al suggested that polymorphisms in the mannose-binding lectin gene are one of the determinants of age-defined risks of CAAs in KD patients, being protective in infants but potentially harmful in patients aged >1 year. 39 Moreover, the clinically heterogeneous features of KD (eg, polymorphous skin rash, cervical lymphadenopathy, and abdominal signs) may be a clue to explore any candidate agents and/or heterogeneous gene-environment interactions modified by patient age.…”
Section: Discussionmentioning
confidence: 99%
“… 37 More recently, an age-stratified genome-wide association study targeting both Korean and Japanese populations suspected a rare non-synonymous SNP (rs4365796) in the lymphoid enhancer binding factor 1 gene to be a susceptibility gene to specifically affect KD patients younger than 6 months of age. 38 Interestingly, Biezeveld et al suggested that polymorphisms in the mannose-binding lectin gene are one of the determinants of age-defined risks of CAAs in KD patients, being protective in infants but potentially harmful in patients aged >1 year. 39 Moreover, the clinically heterogeneous features of KD (eg, polymorphous skin rash, cervical lymphadenopathy, and abdominal signs) may be a clue to explore any candidate agents and/or heterogeneous gene-environment interactions modified by patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility genes for KD (5-16) HLA, HCP5, FCGR2A, BLK, SLC8A1, CD40, NMNAT2, DAB1, COPB2, NAALADL2, IGHV, ZFHX3, NFKBIL1, ERAP1, EBF2, CACNB2, LTA, and LEF1 SNP in SLC8A1 (calcium signaling pathway) can be proof for using calcineurin inhibitors in KD and LEF1) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) to the risk of cardiovascular disease in KD (TIAM1, NEBL, PLCB4/PLCB1, TUBA3C, SLC8A1, PELI1, KCNN2, TIFAB, and AGT) (8,12,(17)(18)(19)(20)(21)(22) and to the risk of intravenous immunoglobulin (IVIG) resistance (BCL2L11 and SAMD9L) (23,24). Involvement of the HLA region in susceptibility to KD has been controversial and has not been replicated across different ancestral groups.…”
Section: Related Risk and Referencesmentioning
confidence: 99%